Pesantren Efektif: Studi Gaya Kepemimpinan Partisipatif - Muhammad Anggung Manumanoso Prasetyo (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2022)
This article aims to describe how participatory leadership styles are applied and contribute substantially to the effectiveness of boarding school management. Research is done using survey data sets. Research is of a descriptive qualitative type. The research took Al-Mujaddid integrated boarding school locus of Sabang-Aceh city. Our analysis shows that participatory leadership becomes a fundamental base in the implementation of the boarding school education system. The effectiveness of participatory leadership styles refers to some aspects, namely (1) decision-making processes; (2) organizational conflict-handling processes; and (3) communication strategies in shaping a positive boarding culture. Research implications for boarding school managers in order to perform variative professional development in all types of leadership. Expectations to participatory leadership style can affect teachers' participation in teaching, mentoring, peer observation, and coaching compared to other types of professional development. The paper proposed a participatory leadership style in the Boarding Cottage, as well as other Islamic education systems that have characteristic similarities in the organization of boarding school education. Recommendations for educational practitioners for ideal leadership in boarding school.